2022
DOI: 10.1101/2022.11.02.514751
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Room-temperature crystallography reveals altered binding of small-molecule fragments to PTP1B

Abstract: Much of our current understanding of how small-molecule ligands interact with proteins stems from X-ray crystal structures determined at cryogenic (cryo) temperature. For proteins alone, room-temperature (RT) crystallography can reveal previously hidden, biologically relevant alternate conformations. However, less is understood about how RT crystallography may impact the conformational landscapes of protein-ligand complexes. Previously we showed that small-molecule fragments cluster in putative allosteric site… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…These differences between room-temperature and cryogenic crystallography structures have been experimentally observed for several proteins. [86][87][88][89][90][91][92][93] A careful analysis of our NQO1 structure has further revealed that residues Tyr128 and Phe232, which play a key role in the function of the protein, [94][95][96][97][98] show an unexpected flexibility within the crystals (Fig. 7(a)).…”
Section: Droplet Generation and Injection Performancementioning
confidence: 99%
“…These differences between room-temperature and cryogenic crystallography structures have been experimentally observed for several proteins. [86][87][88][89][90][91][92][93] A careful analysis of our NQO1 structure has further revealed that residues Tyr128 and Phe232, which play a key role in the function of the protein, [94][95][96][97][98] show an unexpected flexibility within the crystals (Fig. 7(a)).…”
Section: Droplet Generation and Injection Performancementioning
confidence: 99%
“…These tools will be highly applicable to work at ambient temperature and we envisage combined studies using both crystals under cryogenic conditions and at ambient temperature ( Krojer et al, 2020 ). While several studies report ligand binding at room temperature and 100 K ( Maeki et al, 2020 ; Mehlman et al, 2022 ), a full understanding of which protein-ligand interactions are likely to display such differences remains elusive. Similarly benefiting from computational power are docking software and machine learning (ML) algorithms for ligands and drug molecules identification and/or generation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is recognised that data collection under the cryogenic conditions (100 K) that are standard in X-ray crystallography may result in binding modes or interactions that are not fully consistent with those occurring under physiological conditions ( Helliwell, 2020 ). A fascinating example was recently provided by a systematic comparison of the binding of fragments to the enzyme protein tyrosine phosphatase, PTP1B ( Mehlman et al, 2022 ). Here, fragments were soaked into crystals that were then either cryo-cooled conventionally, harvested for room temperature data collection in loops or measured in situ within crystallisation plates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This automation in modeling is needed especially in light of advances in data collection automation and fast detectors. These tools have revolutionized the field of X-ray crystallography, enabling high-temperature datasets, time-resolved experiments, and high-throughput data collection [46][47][48][49][50] . With the ability to capture different conformations, there is a growing demand for methods that can detect protein alternative conformers to extract as much biological information as possible.…”
Section: Simulated Multiconformer Data Illustrate the Convergence Of ...mentioning
confidence: 99%